Environmental Performance Indicators from the Residents’ Perspective: A Case Study of Jerash Governorate - zregat, Dalal; Al-Widian, Safaa; Al-Khasawneh, Heba; Alzqhoul, maysoon; Zeitoun, Mohammad; Matar, Mohammad (Arts and Social Sciences Series, 2026)
objectives: This study seeks to assess environmental performance indicators in Jerash Governorate through a field study that analyzes residents’ perspectives on various environmental indicators, which include waste management, air quality, water quality and sanitation, energy and sustainability, green spaces and urban planning, biodiversity and resource protection, and community participation and governance. Methodology: The study utilized a descriptive–analytical method and a thoroughly validated scientific questionnaire, administered to a sample of 350 respondents representing the Jerash Governorate population in August, September, and October 2025. We implemented arithmetic means, standard deviations, and correlation coefficients to analyze the data and determine how the items were related to their domains. Results: The findings indicated that the average total environmental performance score for Jerash Governorate was 3.07 which signifies a moderate assessment level of 61.4% on a five-point scale. This indicates an acceptable level of environmental awareness, but one that still requires improvement. Air quality ranked first with an average score of 3.41, followed by water quality and sanitation (3.34), energy and sustainability (3.18), and biodiversity (3.15). The lowest mean score was recorded for green spaces and urban planning (2.63).The study revealed no statistically significant differences (α ≤ 0.05) in residents’ perceptions of environmental indicators based on demographic variables such as gender, age, marital status, level of education, income, profession, place of residence, housing type, housing ownership, participation in environmental activities, and family size. Recommendations: The study suggests increasing environmental education and awareness in the Jerash Governorate through schools, scientific conferences, and various local environmental initiatives. It also recommends strengthening infrastructure for recycling and garbage management, the expanding of green spaces, and improving air quality through forestry initiatives. The study also emphasizes the importance of encouraging locals to actively participate in environmental decision-making and supporting community projects. Lastly, it emphasizes how crucial it is to incorporate environmental performance metrics into Jerash City’s urban planning regulations.